2019
DOI: 10.1145/3324888
|View full text |Cite
|
Sign up to set email alerts
|

Failure rates in introductory programming

Abstract: It is a common conception that CS1 is a very difficult course and that failure rates are high. However, until now there has only been anecdotal evidence for this claim. This article reports on a survey among institutions around the world on failure rates in introductory programming courses. The article describes the design of the survey and the results. The number of institutions answering the call for data was unfortunately rather low, so it is difficult to make firm conclusions. It is our hope that this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2
18

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(85 citation statements)
references
References 10 publications
2
63
2
18
Order By: Relevance
“…Promoting effective learning and student success remains a key issue in higher education, particularly in the area of computer science, with high failure rates reported for introductory programming in particular [5,45]. As such, considerable work has been undertaken to understand the factors that have influence on these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting effective learning and student success remains a key issue in higher education, particularly in the area of computer science, with high failure rates reported for introductory programming in particular [5,45]. As such, considerable work has been undertaken to understand the factors that have influence on these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Student dropout and failure are two major problems faced during the teaching-learning process of computer programming at any education level [1]. These disciplines have high failure rates around the world, sometimes achieving over 50% [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Student dropout and failure are two major problems faced during the teaching-learning process of computer programming at any education level [1]. These disciplines have high failure rates around the world, sometimes achieving over 50% [1][2][3][4][5]. According to the literature, many factors may contribute to this low approval rate, such as difficulties related to the required abstraction for the proper development of algorithms, difficulties in problem-solving, and also the early stage, in which the programming courses are placed inside the curricula [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that introductory programming (CS1) courses in higher education have high dropout rates [9], [10]. A worldwide survey on pass rates reported that, on average, only 67% of students complete their CS1 course [11]. Watson & Li expanded on this study, finding that the mean pass rate of CS1 courses is 67.7% and that pass rates have not improved over time [12].…”
Section: A Dropout In Introductory Programming Coursesmentioning
confidence: 87%